Actividad social de la Escuela de Ciencias de la Educación. (UNED, 2024)
De izquierda a derecha aparece Hellen Roxana Valverde Limbrick, Flor María Chacón Cháves, Walter Solano Gutiérrez, Leda María Vásquez Esquivel, Cecilia Balmaceda Alvarado, Fernando Brenes Espinoza, Lester Osorno Membreño